Roles of reactive oxygen species, storage compounds, and endogenous hormones in regulating somatic embryogenesis in blue spruce (Picea pungens Engelm.) - Chen, Shigang; Gao, Fang; Cao, Xi; Dong, Huanyu; Zhan, Yuchen; Zhu, Li-Hua; Tao, Jing (Frontiers in Plant Science, 2026)
Four freshly established cell lines of blue spruce (Picea pungens Engelm.), with different capacities for somatic embryogenesis (SE), were studied to assess their SE formation and maturation, aiming at identifying key factors responsible for the variation in SE potential. We examined dynamic cytological and physiological changes, including morphology and structure, storage substances, antioxidant enzyme activities and endogenous hormone levels. The results showed that cell lines 202, 201, 211 with SE capacity exhibited active metabolic processes and significant increases in superoxide dismutase (SOD) and peroxidase (POD) activities, total protein (TP) and malondialdehyde (MDA) contents across developmental stages. In contrast, the cell line lacking SE capacity showed low or unchanged enzyme activities. These findings suggest that SOD, POD, MDA and TP can serve as physiological markers for identifying SE capacity. During SE development and maturation, endogenous hormone levels (GA, IAA, ABA) remained unchanged in the non-embryogenic cell line. However, in highly embryogenic line, hormone levels generally increased and then decreased, while lines with intermediate and weak SE showed a steady increase. Our findings provide critical insights into optimizing culture media formulations to enhance blue spruce SE maturation, thereby improving efficiencies of elite genotype selection and large-scale clonal propagation. Such advancements are essential for meeting the growing demand for high-quality planting materials in landscape applications and forestry production. Nevertheless, the underlying molecular mechanisms by which reactive oxygen species (ROS) influence SE maturation capacity, as well as the synergistic regulatory interactions among endogenous hormones during different embryo developmental stages, remain insufficiently understood and warrant further investigation. Furthermore, the technological framework and regulatory patterns identified in this study are not limited to blue spruce; the physiological markers and developmental cues elucidated herein may serve as valuable references for SE research in coniferous species. To validate the practical applicability of this approach, comprehensive field trials are required to evaluate the growth performance, adaptability, and stability of SE-derived plants under natural environmental conditions.